2018
DOI: 10.1111/aogs.13306
|View full text |Cite
|
Sign up to set email alerts
|

Association of microRNA‐200c expression levels with clinicopathological factors and prognosis in endometrioid endometrial cancer

Abstract: Expression levels of miRNA-200c might be associated with clinicopathological factors and survival in endometrioid endometrial cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 30 publications
0
13
0
1
Order By: Relevance
“…Wang et al [17] found that in primary or metastatic EC tissues, miR-29b was lower expressed compared with the normal controls, and using miR-29b expression to diagnose EC output 0.976 area under the curve (AUC), with the 96.1% sensitivity and 97.9% specificity, suggesting that lower expression of miR-29b correlated with poor prognosis of EC patients. Similarly, upregulation of miR-200c in endometrioid-EC tissues compared with normal controls was revealed by Wilczynski et al [18]; they also found that lower expression of miR-200c was linked to unfavorable survival.…”
Section: Introductionmentioning
confidence: 59%
“…Wang et al [17] found that in primary or metastatic EC tissues, miR-29b was lower expressed compared with the normal controls, and using miR-29b expression to diagnose EC output 0.976 area under the curve (AUC), with the 96.1% sensitivity and 97.9% specificity, suggesting that lower expression of miR-29b correlated with poor prognosis of EC patients. Similarly, upregulation of miR-200c in endometrioid-EC tissues compared with normal controls was revealed by Wilczynski et al [18]; they also found that lower expression of miR-200c was linked to unfavorable survival.…”
Section: Introductionmentioning
confidence: 59%
“…Lee et al [31] identified the microRNA expression profile related to lymph node status in women with early-stage grade 1–2 endometrial cancer. Wilczynski et al [32] reported aberrant microRNA expression in endometrial carcinoma using formalin-fixed paraffin-embedded (FFPE) tissues. In this study, we found that miR-369-3p was significantly downexpressed in EEC tissues compared to control tissues and that the upregulation of miR-369-3p inhibited EEC cell proliferation via ATG10.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29] However, there are few reports about miR-200c and cervical cancer. To date, no miRNA-4636-related pathway has been reported.…”
Section: Discussionmentioning
confidence: 99%